Rationale of Unfractionated heparin during elective Coronary Angiography - Malla, R; Sharma, R; Rauniyar, B; K.C., MB; Maskey, A; Joshi, D; Hamal, S (Journal of Nepal Health Research Council, 2009)
Background: Unfractionated heparin (UFH) has been conventionally used during coronary angiography (CAG). Whether to use unfractionated heparin or not, has been unanswered. Methods: Hundred patients who underwent CAG through femoral route were assessed. CAG was performed without using unfractionated heparin and embolic or thrombotic event and vascular complications were observed during and after procedure. Results: The right femoral approach was used in 92% of cases and the left in 8%. Those patients who underwent radial route were excluded. Male (65%) were exceeded the female and smoking (50%) was the major predisposing factor. There were no embolic or thrombotic event and vascular complications such as bleeding, heamatoma, pseudoaneurysm formation, A-V fistula and retroperitoneal bleeding during or after procedure. Conclusions: Routine elective CAG have shown no significant complication during or after the procedure without UFH. Key words: angiography, coronary angiography, unfractionated heparin DOI: 10.3126/jnhrc.v7i1.2278 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 42-44